A Survey on Branciari Metric Spaces - Das, Abhishikta; Bag, Tarapada (Communications in Mathematics and Applications, 2023)
The motive of this review article is to collect most of the results on v-generalized metric space and its upto date various generalizations. We try to update the literature for continuous development on the results of v-generalized metric and its generalizations.
Keywords: Metric; v-generalized metric; 2-generalized metric; 3-generalized metric; rectangular b-metric; cone rectangular metric; rectangular S-metric; partial rectangular metric; rectangular M-metric; complex valued rectangular metri; fixed point; compatible topology